Automated 1D Helmholtz coil design for cell biology: Weak magnetic fields alter cytoskeleton dynamics - Abasalt Bahrami; Leonardo Y. Tanaka; Ricardo C. Massucatto; Francisco R. M. Laurindo; Clarice D. Aiello (PLoS ONE, 2025)
Evidence of the biological impacts of weak magnetic fields have been reported for more than fifty years. However, research progress on such effects has been hampered by a lack of systematics in most experiments. Efforts to increase the systematics in such cell biology experiments must include the capability of producing fields that can be automatically adjusted and that are stable throughout an experiment’s duration, usually operating inside an incubator. Here, we report on the design of a fully automated 1D Helmholtz coil setup that is internally water cooled, thus eliminating any confounding effects caused by temperature fluctuations. The coils also allow cells to be exposed to magnetic fields from multiple directions through automated controlled rotation. Preliminary data, acquired with the coils placed inside an incubator and on a rat vascular smooth muscle cell line, confirm previous reports that both microtubule and actin polymerization and dynamics are altered by weak magnetic fields.